Copper-coordination induced fabrication of stimuli-responsive polymersomes from amphiphilic block copolymer containing pendant thioethers. Issue 21 (6th May 2021) - Dong, Shuqi; Liu, Li; Zhao, Hanying
Abstract : Cu 2+ -Containing hybrid polymersomes were fabricated via a co-assembly approach. The polymersomes exhibited stimuli-responsiveness to the competitive ligand and H2 O2 /GSH and mediated a Fenton-like reaction to produce ˙OH. Abstract : In this work, we synthesized oxidation-responsive amphiphilic block copolymers PEG45 - b -P(MET/PBC) n bearing pendant phenylboronic ester carbamate (PBC) and thioether moieties in the hydrophobic block by RAFT polymerization and post-polymerization modification. As the hydrophobic block length increased, the polymeric self-assemblies underwent a morphological transition from spherical micelles to worm-like micelles to bilayered polymersomes. Triggered by H2 O2, the polymersomes disintegrated because of the oxidation of thioether to sulfoxides and the decomposition of PBC moieties. Taking advantage of the thioether–copper coordination capability, the hybrid polymersomes with Cu 2+ -cross-linked membrane were fabricated via the co-assembly of the block copolymer with Cu 2+ ions, driven by the coordination interactions between the hydrophobic block and Cu 2+ ions. The metal–ligand interaction endows the hybrid polymersomes with a responsive property to the competitive ligand. In the presence of glutathione (GSH) (or sodium ascorbate) and H2 O2, Cu + ions were in situ produced via the reduction of the entrapped Cu 2+ ions and subsequently initiated a Fenton-like reaction to generate hydroxyl radicals. The catalytic activity of the hybrid polymersomes-mediated Fenton-like reaction was evaluated by the oxidation of terephthalic acid and the degradation of methylene blue, respectively. In the presence of H2 O2 and GSH, the hybrid polymersomes underwent a shape change and transformed into a mixture of spherical micelles and worm-like micelles.